Aerobic oxidation of benzyl alcohols through biosynthesized palladium nanoparticles mediated by Oak fruit bark extract as an efficient heterogeneous nanocatalyst. Issue 44 (1st November 2017) - Veisi, Hojat; Hemmati, Saba; Qomi, Mahnaz
Graphical abstract: Highlights: Green synthesis of Pd nanoparticles using Oak fruit bark extract was introduced. The biosynthesized Pd NPs show good activity in the oxidation of alcohols. The products were produced in excellent yields under mild conditions. The catalyst can be reused several consecutive cycles. Abstract: In this study, green synthesis of Pd nanoparticles (NPs) is outlined through application of Oak fruit bark extract as a reducing, capping and stabilizing agent. The characteristics and properties of the biosynthesized Pd NPs were revealed by FESEM, EDX, XRD, TEM, UV–Vis, and FT-IR spectroscopies. So that, UV–Vis spectroscopy of the Pd colloidal solution confirmed reduction of Pd ions, and XRD and TEM analysis identified fcc unit cell structure forming 5–7 nm spherical Pd NPs. Furthermore, catalytic activity of the prepared catalyst was investigated through aerobic oxidation of alcohols, as model reactions. Catalytic evaluations demonstrated achievement of good yields from primary and secondary benzyl alcohols. In general, the devised synthesis method is advantageous from several perspectives. For example, the synthesized catalysts give high product yields and are efficient, they eliminate the need for surfactant, chemical reductants, ligand and organic solvents, the approach is economically inexpensive, it results in cleaner reaction profiles, application of the simply prepared heterogeneous catalyst is convenient, and the catalyst is recoverable and reusable for at least six times without any significant loss of its catalytic activity.